Iron Porphyrin Carbene Catalytic Intermediates: Structures, Mössbauer and NMR Spectroscopic Properties, and Bonding() - Khade, Rahul L. (2014)
Iron porphyrin carbenes (IPCs) are thought to be intermediates involved in the metabolism of various xenobiotics by cytochrome P450, as well as in chemical reactions catalyzed by metalloporphyrins and engineered P450s. While early work proposed IPCs to contain Fe(II), more recent work invokes a double bond description of the iron carbon bond, similar to that found in Fe(IV) porphyrin oxenes. Here, we report the first quantum chemical investigation of IPC Mössbauer and NMR spectroscopic properties, as well as their electronic structures, together with comparisons to ferrous heme proteins and an Fe(IV) oxene model. The results provide the first accurate predictions of the experimental spectroscopic observables as well as the first theoretical explanation of their electrophilic nature, as deduced from experiment. The preferred resonance structure is Fe(II)←{:C(X)Y}(0) and not Fe(IV)={C(X)Y}(2-), a result that will facilitate research on IPC reactivities in various chemical and biochemical systems.